Self‐Healing: Continuous Self‐Healing Life Cycle in Vascularized Structural Composites (Adv. Mater. 25/2014). (July 2014) - Patrick, Jason F.; Hart, Kevin R.; Krull, Brett P.; Diesendruck, Charles E.; Moore, Jeffrey S.; White, Scott R.; Sottos, Nancy R.
<x xml:space="preserve">Abstract</x> By incorporating three‐dimensional microvascular networks within a woven glass fiber‐reinforced polymer composite N. R. Sottos, S. R. White, and co‐workers demonstrate on page 4302 the full recovery (>100%) of mode‐I fracture resistance after multiple damage events. This optical image of a fracture plane reveals efficient delivery, mixing and polymerization of the fluorescently dyed, two‐part reactive healing chemistry. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>